PENGGUNAAN MULTIMEDIA INTERAKTIF BERBASIS VIDEO PRESENTASI CANVA TERHADAP DAYA TARIK BELAJAR SENI BUDAYA SISWA DI SMP ST. MARIA AEK RAJA - Yohanan Nababan; Eben Haezarni Telaumbanua; Roy Josep M Hutagalung; Testi Bazarni Zebua; Diana Martini Situmeang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the use of interactive multimedia based on Canva video presentations in enhancing students' learning interest in Cultural Arts for Grade VIII B students at SMP ST. Maria Aek Raja. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The research subjects were Grade VIII B students and the Cultural Arts teacher. The results indicate that the implementation of Canva-based video presentations increased students’ engagement, attention, and learning motivation. The integration of text, images, animations, audio, and video made the learning process more attractive and less monotonous. Students became more active in discussions, more confident in expressing their opinions, and better able to understand visual and abstract materials. Although there were challenges such as unstable internet connections and limited supporting facilities, the benefits of using Canva outweighed the obstacles. Therefore, interactive multimedia based on Canva video presentations has proven effective in increasing students’ learning interest in Cultural Arts and supporting the creation of creative and innovative learning environments.